Implementation of Equitable Use and Flexibility of Use in the Design of Public Housings in Jakarta, Indonesia - Satwiko Aryesti Maulana; Maria Immaculata Ririk Winandari; Julindiani Iskandar (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2022)
Population growth happens quickly in Indonesia, especially in Jakarta. With reduced land due to infrastructure development, population growth does not go parallel with the need for housing, which should be a basic need for every human being. This makes the construction of residential houses arranged vertically called public housing. It can reduce land use and create urban open spaces. Public housing should be based on an inclusive design approach that considers human diversity. The design of public housing in Indonesia has not met the needs of all humans, especially in the aspect of all ages and disabilities. The design of the building is still not based on the togetherness of user activities. In the design, it is expected that the use is carried out fairly, which is fair for users and flexibility in space. Aspects of equitable use by pedestrian access and facilities, along with space flexibility based on expandability, convertibility, and versatility. The method used is a qualitative method with the exploration of three cases of public housings. The variables used are inclusive design aspects related to equitable use and flexibility in use. The results reveal that public housing is recommended according to equitable use aspects, inclusive design factors with pedestrian access that is easy to understand and accessible to elderly users and wheelchairs, and affordable facilities. Spaces can be built in the long term with space flexibility, such as multifunctional communal spaces, expansion of spaces near public spaces for unexpected uses, as well as shared use for all users.